The Relationship between Self-Compassion and Social Support with Loneliness in Muslim Adolescents in Surakarta - Cahyani, Desinta Tri; Karyani, Usmi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Loneliness is a widespread psychological and social problem that affects individuals across various developmental stages, but it is particularly pronounced during adolescence. Adolescence is a transitional period characterized by identity exploration, heightened emotional sensitivity, and the search for belonging within peer groups and communities. During this stage, adolescents experience changes in both biological and social dimensions, including increased independence from parents, reliance on peer relationships, and pressures associated with academic and personal achievements. While these transitions are normal and expected, they can also create a sense of vulnerability that contributes to feelings of loneliness. Loneliness, defined as the subjective perception of being socially isolated or disconnected despite the desire for meaningful relationships, has been found to negatively impact adolescents' psychological well-being. Previous research has indicated that prolonged loneliness during adolescence can lead to detrimental outcomes, including depressive symptoms, low self-esteem, academic difficulties, and even suicidal ideation. This makes the study of loneliness in adolescents not only relevant but also urgent. Several factors contribute to the experience of loneliness among adolescents. Two of the most important psychological and social factors are self-compassion and social support. Self-compassion refers to the ability to treat oneself with kindness, maintain mindful awareness of one's experiences, and recognize that suffering and imperfection are part of the shared human experience. Adolescents with higher self-compassion are less likely to engage in harsh self-criticism, less vulnerable to negative emotional spirals, and more capable of accepting personal shortcomings in a constructive way. This self-directed kindness allows them to be more resilient in the face of social rejection or academic stress, both of which are common triggers of loneliness. Meanwhile, social support represents the perception of care, encouragement, and assistance received from family, peers, and significant others. It is a critical external factor that fosters a sense of belonging and security, reinforcing an adolescent's place within a community. For adolescents living in a collectivist culture such as Indonesia, where family and community bonds are highly valued, social support plays an especially important role in buffering against loneliness. While many studies have examined the role of self-compassion and social support in reducing loneliness, most research has been conducted in Western contexts. In the Indonesian context, and particularly among Muslim adolescents, empirical research on this issue remains limited. Religion and cultural values may influence how self-compassion and social support are perceived and experienced. For instance, Islamic teachings emphasize compassion toward oneself and others, as well as the importance of community and family ties. Thus, it is necessary to test empirically how self-compassion and social support function as protective factors against loneliness in Muslim adolescents in Surakarta, a city in Central Java, Indonesia, that reflects both traditional and modern cultural influences. This research seeks to provide empirical evidence on the relationship between these variables, offering insights into the unique developmental and cultural experiences of adolescents in this context. The present study aimed to examine the relationship between self-compassion and social support with loneliness among Muslim adolescents in Surakarta. By focusing on Muslim adolescents, this study not only addresses the general developmental aspects of adolescence but also takes into account religious and cultural values that may shape the dynamics of psychological well-being. The study used a quantitative correlational design to analyze the extent to which selfcompassion and social support predict levels of loneliness in the target population. The respondents consisted of 547 Muslim adolescents residing in Surakarta. The sample included 236 males and 311 females, with an average age of 16.33 years. Participants were recruited through schools in the Surakarta area after obtaining permission from the local education office and relevant school authorities. Ethical approval was secured from the Health Research Ethics Committee of RSUD Dr. Moewardi (No. 576 / III / HREC / 2025), ensuring that the study complied with research ethics standards. Informed consent was also obtained from participants and their guardians prior to participation. Data collection was carried out using an online survey distributed through Google Forms, a method chosen to facilitate efficient access to a large number of adolescents across different schools. Three measurement instruments were used in this study: the UCLA Loneliness Scale Version 3 (Russell, 1996), the Self-Compassion Scale (Neff, 2003), and the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988). All instruments had been adapted into Indonesian and validated for psychometric soundness in prior research. The UCLA Loneliness Scale consisted of 20 items rated on a 4-point Likert scale, measuring the subjective experience of loneliness. The Self-Compassion Scale contained 26 items rated on a 5-point Likert scale, covering six dimensions: self-kindness, selfjudgement, mindfulness, over-identification, common humanity, and isolation. The Multidimensional Scale of Perceived Social Support included 12 items rated on a 7-point Likert scale, assessing support from family, friends, and significant others. Validity and reliability tests confirmed that the instruments were appropriate for use, with Cronbach's Alpha values of 0.837 for loneliness, 0.738 for self-compassion, and 0.889 for social support, indicating good internal consistency. Data were analyzed statistically using multiple linear regression with SPSS version 22. Prior to hypothesis testing, classical assumption tests were conducted, including normality, linearity, multicollinearity, and heteroscedasticity tests, to ensure the suitability of the data for regression analysis. The regression model was then tested using the F-test to examine the overall significance, while t-tests were employed to assess the individual contributions of each predictor variable. The results revealed a significant overall relationship between self-compassion and social support with loneliness, as indicated by the regression model (F = 125.061; p < 0.05). Both self-compassion and social support individually showed significant negative relationships with loneliness. Specifically, self-compassion was negatively correlated with loneliness (t = -7.778; p < 0.05), suggesting that adolescents with higher selfcompassion were less likely to experience loneliness. Similarly, social support was negatively correlated with loneliness (t = -10.233; p < 0.05), indicating that adolescents who perceived stronger social support from their family, friends, and significant others were less likely to feel lonely. The descriptive analysis categorized the level of loneliness among Muslim adolescents in Surakarta as moderate, highlighting that while loneliness is not at an extreme level, it remains a meaningful issue that warrants attention. These findings support the theoretical understanding that both internal resources, such as self-compassion, and external resources, such as social support, serve as protective factors against loneliness. Adolescents with high self-compassion are more likely to cope with negative self-perceptions and accept personal imperfections without harsh self-judgement. This ability allows them to regulate emotions more effectively and maintain psychological balance in the face of social challenges. In parallel, adolescents who perceive strong social support feel more connected, valued, and cared for within their social networks, reducing the risk of loneliness. In the context of Muslim adolescents in Surakarta, the findings resonate with cultural and religious values that emphasize compassion and community. Islamic teachings encourage believers to be gentle and forgiving toward themselves, as well as to engage actively in social bonds, both of which align with the roles of self-compassion and social support in mitigating loneliness. From a practical standpoint, the findings of this study suggest several strategies to address adolescent loneliness. Schools, families, and community organizations can play a vital role in fostering self-compassion and enhancing social support. For example, mindfulness-based interventions and journaling activities may help adolescents cultivate self-awareness and practice self-kindness, thereby increasing their self-compassion. Positive affirmations and self-reflection exercises can also be incorporated into daily routines to build resilience against negative emotions. At the same time, efforts to strengthen social support networks should focus on enhancing communication and trust within families, encouraging adolescents to participate in peer groups and extracurricular activities, and building supportive community structures that emphasize collective care. By addressing both the personal and social dimensions of adolescent development, such interventions can significantly reduce the risk of loneliness. In conclusion, this study demonstrated that self-compassion and social support are significant negative predictors of loneliness among Muslim adolescents in Surakarta. Both factors, acting independently and together, reduce the likelihood of experiencing loneliness. While the overall level of loneliness in the sample was categorized as moderate, the findings underscore the importance of fostering self-compassion and strengthening social support networks in order to promote adolescents' psychological well-being. This research contributes to the understanding of loneliness in the Indonesian cultural and religious context and highlights the need for holistic approaches that address both individual and environmental factors. Future studies may consider longitudinal designs to examine causal relationships and explore other potential protective factors, such as resilience, coping strategies, and religious involvement, to gain a more comprehensive understanding of adolescent loneliness. Ultimately, this study emphasizes the value of nurturing both inner resources and external support systems to ensure the healthy psychosocial development of adolescents.